1977
DOI: 10.1007/bf02207841
|View full text |Cite
|
Sign up to set email alerts
|

Food quality and the heterogeneous spatial distribution of meiofauna

Abstract: Several different experimental approaches were used to examine recruitment of benthic meiofauna to patches of selected species of algae. In one approach algal-coated, baited slides were incubated in a salt marsh littoral benthos. The second approach employed patches of algae arrayed equidistantly around art inoculum of meiofauna in a petri dish. Meiofauna were shown to be selectively recruited to patches of some species of algae but not to others. The evidence obtained supports a hypothesis that selective recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
3

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 23 publications
0
31
0
3
Order By: Relevance
“…dentatum migrated into the macrophytodetritus accumulation to avoid low oxygen levels in the sediment underneath or to search for more accessible food. Harpacticoids are known to feed on a wide variety of food sources (Hicks and Coull, 1983;Lee et al, 1977), displaying species-specific food preferences (Buffan-Dubau and Carman, 2000;De Troch et al, 2012;Decho and Castenholz, 1986;Pace and Carman, 1996;Wyckmans et al, 2007). Hicks and Coull (1983) stated that the existence of a wide variety of morphologically similar species in one habitat is allowed as a consequence of harpacticoids' selective feeding.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…dentatum migrated into the macrophytodetritus accumulation to avoid low oxygen levels in the sediment underneath or to search for more accessible food. Harpacticoids are known to feed on a wide variety of food sources (Hicks and Coull, 1983;Lee et al, 1977), displaying species-specific food preferences (Buffan-Dubau and Carman, 2000;De Troch et al, 2012;Decho and Castenholz, 1986;Pace and Carman, 1996;Wyckmans et al, 2007). Hicks and Coull (1983) stated that the existence of a wide variety of morphologically similar species in one habitat is allowed as a consequence of harpacticoids' selective feeding.…”
Section: Harpacticoid Copepod Species Assemblage In Detritusmentioning
confidence: 99%
“…Further, food resources used by copepod species may change ontogenetically (Decho & Fleeger 1988a), seasonally (Lee et al 1976), or over shorter time scales such as a tidal cycle (Decho 1988, Souza-Santos et al 1995. Exploitation of different microbial food sources by copepods has been suggested as an explanation for their spatially and temporally heterogeneous distributions (Lee et al 1977, Reiper 1984, Carman & Thistle 1985, Decho & Castenholz 1986, Decho & Fleeger 1988b. Mar Ecol Prog Ser 143: 77-86,1996 Few stud.ies have addressed how microbial food resources are exploited by natural harpacticoid copepod communities.…”
Section: Introductionmentioning
confidence: 99%
“…Mar Ecol Prog Ser 143: 77-86,1996 Few stud.ies have addressed how microbial food resources are exploited by natural harpacticoid copepod communities. Field studies (Lee et al 1977, Carman & Thistle 1985, Decho & Castenholz 1986) have provided evidence of interspecific feeding differences among harpacticoid copepods as well as positive spatial correlations between the distribution of copepods and their potential microbial food resources (Decho & Fleeger 198813, Blanchard 1991, Montagna et al 1995. Other field studies , Alongi 1988, however, have detected no correlation between harpacticoid copepods and their microbial food resources.…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are known from both laboratory and field studies to be an important food resource of many meiobenthc harpacticoids (Lee et al 1976, Sellner 1976, Brown & Sibert 1977, Harris 1977, Lee et al 1977, Vanden Berghe & Bergmans 1981, Ustach 1982, Admiraal et al 1983, Montagna 1984, Carman & Thistle 1985, Lee et al 1985, Chandler 1986, Decho 1986, Decho & Castenholz 1986, Nilsson 1987, Decho & Fleeger 1988a. Laboratory studies (Decho 1986) have indicated that certain harpacticoids consume diatom food resources at different rates over portions of a simulated tidal cycle.…”
Section: Introductionmentioning
confidence: 99%